Planificación financiera familiar y su incidencia en el nivel de vida del cantón Palanda. - Jiménez Álvarez, Maritza Carmen (2023)
The general objective of this thesis project is to conduct a study of family financial planning and its relationship with the standard of living in the canton of Palanda. The Family Financial Planning (FFP), is a factor of great importance worldwide, therefore, seeks to improve the ability to manage money in an appropriate manner, allowing to understand the appropriate methods for the control of income and expenses of a family unit, helping to avoid possible economic deficits that may arise in the future. Deficits that may arise in the future. Based on this, a methodology with a mixed approach was used for the development of the study, oriented to investigate and deepen the incidence of FFP in the standard of living of families in the canton of Palanda in the province of Zamora Chinchipe; in addition, the survey technique was used to collect relevant information related to the variables used in the research (family financial planning vs. standard of living). The sample of this study consisted of 337 households belonging to the canton of Palanda, aged 15 years and older. Among the main findings of the curriculum integration work, 50.74% of Palanda families do keep track of the monthly income of each household; likewise, it is observed that the most preferred method for financial planning is paper and/or notebook, which represents 32.5%; however, other methods used by households in the canton in parallel are Excel spreadsheets and mobile applications, corresponding to 53.8%. Similarly, it is evident that financial planning does not directly influence the level of household savings, since the level of savings depends on the monthly income of the families, so that of the families surveyed that do plan, 50. 28% tend to have an optimal level of savings; on the other hand, the PFF does influence the level of indebtedness in households, because indebtedness is generated by lack of financial culture, investing or making unnecessary expenses, which is the case of 49% of the population that does not plan belonging to the canton of Palanda are in a state of overindebtedness.